2018
DOI: 10.1146/annurev-physchem-050317-014216
|View full text |Cite
|
Sign up to set email alerts
|

Computational Design of Clusters for Catalysis

Abstract: When small clusters are studied in chemical physics or physical chemistry, one perhaps thinks of the fundamental aspects of cluster electronic structure, or precision spectroscopy in ultracold molecular beams. However, small clusters are also of interest in catalysis, where the cold ground state or an isolated cluster may not even be the right starting point. Instead, the big question is: What happens to cluster-based catalysts under real conditions of catalysis, such as high temperature and coverage with reag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 155 publications
2
70
0
Order By: Relevance
“…The catalysts were prepared by depositing size‐selected, originally metallic, ligand‐free Pd and Cu clusters from the gas phase on alumina, titania, or ultrananocrystalline diamond (UNCD) support, with the goal to explore the effect of cluster size and the nature of the support on catalytic activity and selectivity . The catalysts were tested and characterized using a multiprobe in situ approach that combined temperature programmed reaction (TPRx), grazing incidence X‐ray absorption spectroscopy (GIXAS), and grazing incidence small‐angle X‐ray scattering (GISAXS), to find a correlation between catalytic performance and the oxidation state of the metal under realistic reaction conditions of temperature and pressure, while also allowing simultaneous monitoring of the sintering resistance of the clusters . Further details on the experimental methods are given in in Experimental Methods section and in the Supporting Information (SI).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The catalysts were prepared by depositing size‐selected, originally metallic, ligand‐free Pd and Cu clusters from the gas phase on alumina, titania, or ultrananocrystalline diamond (UNCD) support, with the goal to explore the effect of cluster size and the nature of the support on catalytic activity and selectivity . The catalysts were tested and characterized using a multiprobe in situ approach that combined temperature programmed reaction (TPRx), grazing incidence X‐ray absorption spectroscopy (GIXAS), and grazing incidence small‐angle X‐ray scattering (GISAXS), to find a correlation between catalytic performance and the oxidation state of the metal under realistic reaction conditions of temperature and pressure, while also allowing simultaneous monitoring of the sintering resistance of the clusters . Further details on the experimental methods are given in in Experimental Methods section and in the Supporting Information (SI).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the global minimum alone cannot accurately represent the catalyst. Less stable isomers are likely to be more chemically reactive and therefore cannot be ignored . In Table , we specify the number of thermally‐relevant isomers of supported clusters and the average charges on the metal atoms.…”
Section: Computational Sectionmentioning
confidence: 99%
“…In this section, we discuss the methods and models that are mainly being used in the nanocluster catalysis community, and emphasize why we need to be careful when using some of these models to describe the catalytic properties when the catalytic interface is so dynamic. It is clear that finding the correlation between catalyst morphology and catalytic performance is essential to designing new catalysts with enhanced efficiency . Hence, a major tool is global optimization, already discussed above, to be used for the finding of both the global and the accessible local minima of cluster catalysts.…”
Section: Notes On the Computational Methodsmentioning
confidence: 99%
“…Always being a nontrivial task, it is truly complicated for surface‐supported cluster catalysts. High temperatures (~300°C in thermal catalysis), coverage with adsorbates, or the presence of electrolyte and electrochemical potential (in electrocatalysis) significantly affect the structure of both the nanocluster (due to its dynamic nature) and the support (by causing defects) . Given that, it is crucial to develop an accurate, yet computationally practical model to describe the system .…”
Section: The Global Minimum Structure Of the Cluster Catalyst: Not Trmentioning
confidence: 99%
“…Metal clusters often exhibit catalytic activities different from bulk. Such nanocatalysts have therefore attracted much attention as candidates of alternatives to conventional heterogeneous catalysts . Density functional theory (DFT) calculations have indicated that existence of low‐coordinated metal atoms makes metal clusters more reactive than solid surfaces in many catalytic bond activation reactions .…”
Section: Introductionmentioning
confidence: 99%